Efektivitas Green Roof Untuk Mengurangi Limpasan Hujan: Efektivitas Green Roof - Wahidah, Noor (Jurnal Teknologi Infrastruktur, 2023)
Land use hange dua to housing development can indirectly damage water catchment areas. One of the impacts is rain runoff that is greater than the absorption capacity of the soil, causing puddles immediately after the rain. Based on these problems, idea to test the effectiveness using a green roof compared to ordinary zinc roof against rain runoff. study aims to measure the comparison runoff discharge from ordinary zinc roofs and green roofs, analyze effectiveness of green roofs with slopes 10o, 15o and 25o, and find out the application of green roofs can provide alternatives to the rate of rain runoff. in the green roof use elephant grass vegetation with a size of 100 cm x 100 cm and artificial rain testing using a simple rainfall simulator assembled using a pipe with a size of 100 cm x 100 cm with a pipe diameter 1/2 inch. Tests using green roofs with slope variations 10o, 15o and 25o and variations in rain duration times 3, 5 and 8 minutes. After testing with different slope variations, the effective slope in this study is 10o slope with a percentage value obtained at a rain duration of 3 minutes is 95%, with a rain duration of 5 minutes is 93%, and a rain duration of 8 minutes is 90% and 10o slope can reduce quite high and the volume of rain runoff produced is small. Keywords: Zinc Roof, Green Roof, Slope, Rain Runoff